TiO2 powder synthesized via the solvothermal method and enhanced photocatalytic degradation of methomyl - Jansanthea P. (2017)
© 2016 Trans Tech Publications, Switzerland. TiO 2 powder was synthesized via the solvothermal method and characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). Single phase anatase was obtained without calcination steps. The particle was irregular in shape with average particle size of 1.0 μm. The characteristic X–ray radiation of element was show titanium at 4.510 keV and 4.931 keV and oxygen at 0.523 keV. The photocatalytic degradation of methomyl in aqueous solution over TiO 2 powder under UV irradiation was determined by UV-Vis spectroscopy. The influence of the amount of TiO 2 powder for photocatalytic degradation of methomyl and rate constant were determined. The optimum condition for photocatalytic degradation of methomyl over TiO 2 powder was obtained at 0.05 g.L -1 for the amount of TiO 2 powder in 60 min. The degradation rate constant at the optimum condition was 0.0243 min -1 .